Auditory complaints and audiologic assessment in children with surgically repaired cleft lip and palate - Lourenço Cerom, Jaqueline; Renata José, Maria; Azenha, Fabiana de Souza Pinto; Macedo, Camila de Cássia; Alvarenga, Kátia de Freitas; Lopes, Andréa Cintra; Feniman, Mariza Ribeiro (International Archives of Otorhinolaryngology, 2013)
Introduction: At the initial consultation, the speech–language pathologist and audiologist may consider possible diagnostic hypotheses based on the child's history and the parents' complaint.Aim: To investigate the association of hearing complaints with the findings obtained in the conventional audiologic assessment in children with cleft lip and palate. Retrospective study.Methods: We analyzed medical charts of 1000 patients with cleft lip and palate who underwent surgical repair between 1988 and 1995 at a mean age of 6 years 8 months. We excluded charts with records of inconsistent audiological responses and charts with missing data for any of the audiologic evaluations considered. Thus, the sample consisted of 393 records.Results: Two hundred thirty-nine patients presented hearing loss in one or both ears, but only 3.8% reported hearing complaints. The most frequent were otorrhea followed by otalgia. There was no statistical significance between the complaint and gender (p = 0.26) nor between the complaint and hearing loss (p = 0.83).Conclusion: This study showed no association between the hearing complaint and the conventional audiologic assessment.
Keywords: Hearing Loss; Cleft Palate; Child; Audiometry; Hearing